The Effect Of Competence And Utilization Of Information Technology On Tax Auditor Performance With Motivation As Variable Of Moderation - Khairani, Soraya; Ratnawati, Vince; Andreas, Andreas (International Journal of Economic, Business & Applications, 2021)
This study has several objectives, first to analyze the effect of competence and utilization of information technology on the performance of tax auditors. Second, analyze the influence of competence and utilization of information technology of tax auditors which is moderated by motivation. The population of this research are 166 tax auditors in the Riau Directorate General Regional Office environment as many as 153 people and the sampling method is saturated samples. Data processed is primary data obtained by processing questionnaire data. Data processed is primary data obtained by processing questionnaire data and were analyzed with the help of the Smart PLS Version 3.2.8 program. The results of the study prove that competence and utilization of information technology has significantly affect to performance of the tax auditors. The last, motivation moderates the effect of competence and utilization of information technology to the performance of tax auditors.